Is Ghana¿s pro-poor health insurance scheme really for the poor? Evidence from Northern Ghana - Akazili, J.; Welaga, P.; Bawah, A.; Achana, F.S.; Oduro, A.; Awoonor-Williams, J.K.; Williams, J.E.; Aikins, M.; Phillips, J.F. (My University, 2014)
Abstract Background Protecting the poor and vulnerable against the cost of unforeseen ill health has become a global concern culminating in the 2005 World Health Assembly resolution urging member states to ensure financial protection to all citizens, especially children and women of reproductive age. Ghana provides financial protection to its citizens through the National Health Insurance Scheme (NHIS). Launched in 2004, its proponents claim that the NHIS is a pro-poor financial commitment that implements the World Health Assembly resolution. Methods Using 2011 survey data collected in seven districts in northern Ghana from 5469 women aged 15 to 49 the paper explores the extent to which poor child-bearing age mothers are covered by the NHIS in Ghana’s poorest and most remote region. Factors associated with enrolment into the NHIS are estimated with logistic regression models employing covariates for household relative socio-economic status (SES), location of residence and maternal educational attainment, marital status, age, religion and financial autonomy. Results Results from the analysis showed that 33.9 percent of women in the lowest SES quintile compared to 58.3 percent for those in the highest quintile were insured. About 60 percent of respondents were registered. However, only 40 percent had valid insurance cards indicating that over 20 percent of the registered respondents did not have insurance cards. Thus, a fifth of the respondents were women who were registered but unprotected from the burden of health care payments. Results show that the relatively well educated, prosperous, married and Christian respondents were more likely to be insured than other women. Conversely, women living in remote households that were relatively poor or where traditional religion was practised had lower odds of insurance coverage. Conclusion The results suggest that the NHIS is yet to achieve its goal of addressing the need of the poor for insurance against health related financial risks. To ultimately attain adequate equitable financial protection for its citizens, achieve universal health coverage in health care financing, and fully implement the World Health Assembly resolution, Ghana must reform enrolment policies in ways that guarantee pre-payment for the most poor and vulnerable households.